A Cofinancing Demand-Oriented Model of Continuous Vocational Training: the Spanish Case - Voirol-Rubido, Isabelq (Swiss Journal of Educational Research, 2017)
This article aims to analyse the potential of a continuous vocational training (CVT) demand oriented financing system. Based on a secondary data analysis combining quantitative and qualitative methodologies, it analyses the quality of the Spanish system focusing on its efficiency, equity of access and potential to incentive employees to be trained between 2004 and 2011. The results suggest that the system has positive effects on Spanish workers’ access to CVT. However, it cannot counter the training instrumentalization by employers, nor can it thwart the opportunity costs impact on the decision to invest in CVT which obviously penalises training investment.